Management‌ ‌of‌ ‌dentofacial‌ ‌trauma‌ ‌in‌ ‌an‌ ‌adolescent‌ ‌patient:‌ ‌The‌ ‌ conservative‌ ‌and‌ ‌the‌ ‌preservative‌ ‌approach‌ - Rai, Amita; Koirala, Bandana; Dali, Mamta; Shrestha, Sneha (Journal of Kathmandu Medical College, 2020)
Mandibular fractures are one of the most frequent occurrences in maxillofacial trauma. Age of the patient, presence of additional injuries, co-morbid diseases of the patient, trauma type, and localization of the fracture must be considered while choosing the treatment strategy. A 12-year-old female patient reported with the complaint of fallen teeth due to trauma three days back. Clinical and radiographic findings revealed symphysis fracture with left sided parasymphysis and subcondylar fracture along with avulsion of 11 and 21. Intermaxillary fixation was done with Erich arch bars and elastics for the management of mandibular fracture, and rehabilitation of edentulous space was done using the avulsed teeth as pontics which were bonded to the adjacent abutment teeth using fiber-reinforced composite.